THE INFLUENCE OF HUMAN RESOURCE TRAINING AND MAINTENANCE ON THE PERFORMANCE OF PRODUCTION DEPARTMENT EMPLOYEES MEDIATED BY JOB SATISFACTION (STUDY AT PT KARYA PRIMA ANDALAN IN BATU BARA DISTRICT) - Putri Nurfadia; Sjahril Effendy; Muis Fauzi Rambe (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The objective of this study is to test and analyze the impact of training, talent retention, and job satisfaction on employee performance. This study also investigates the impact of talent training and retention on job satisfaction and how job satisfaction affects the relationship between training, talent retention, and employee performance. Associative survey technique is used in this study with a sample of 76 respondents who are employees of PT Karya Prima Andalan, Batu Bara Regency. Data collection technique involves the use of questionnaires and data analysis is performed using partial least squares (SEM-PLS). According to the findings, training, talent retention, and job satisfaction have a significant impact on employee performance. Furthermore, talent training and retention significantly affect job satisfaction. Talent training and retention also significantly affect employee performance with job satisfaction acting as a mediating variable.